Home-Based Therapy After Stroke Using the Hand Spring Operated Movement Enhancer (HandSOME II) - Casas, Rafael; Sandison, Melissa; Nichols, Diane; Martin, Kaelin; Phan, Khue; Chen, Tianyao; Lum, Peter S. (Frontiers in Neurorobotics, 2021)
We have developed a passive and lightweight wearable hand exoskeleton (HandSOME II) that improves range of motion and functional task practice in laboratory testing. For this longitudinal study, we recruited 15 individuals with chronic stroke and asked them to use the device at home for 1.5 hours per weekday for 8 weeks. Subjects visited the clinic once per week to report progress and troubleshoot problems. Subjects were then given the HandSOME II for the next 3 months, and asked to continue to use it, but without any scheduled contact with the project team. Clinical evaluations and biomechanical testing was performed before and after the 8 week intervention and at the 3 month followup. EEG measures were taken before and after the 8 weeks of training to examine any recovery associated brain reorganization. Ten subjects completed the study. After 8 weeks of training, functional ability (Action Research Arm Test), flexor tone (Modified Ashworth Test), and real world use of the impaired limb (Motor Activity Log) improved significantly (p<.05). Gains in real world use were retained at the 3-month followup (p=.005). At both post training and followup time points, biomechanical testing found significant gains in finger ROM and hand displacement in a reaching task (p<.05). Baseline functional connectivity correlated with gains in motor function, while changes in EEG functional connectivity paralleled changes in motor recovery. HandSOME II is a low-cost, home-based intervention that elicits brain plasticity and can improve functional motor outcomes in the chronic stroke population.